Unlocking the secrets of bedtime procrastination: the role of self–control, chronotype, and future time perspective in Malaysian young adults - Tan Hor Yinn; Isaac Law Lik Jun; Leong Syn Jieh; Nurul Iman Abdul Jalil (Penerbit Universiti Kebangsaan Malaysia, 2024)
Bedtime procrastination, a voluntary behavior of sleeping later than the intended time, is a prevalent issue in modern society, yet being understudied in Malaysia. It brings health interfering impacts such as sleep deficiency, which in turn could affect the physical and mental health of the individual. This research examined the predictive effects of self-control, chronotype, and future time perspective on bedtime procrastination, with the hypothesis that self-control, chronotype, and future time perspective could negatively predict bedtime procrastination. A quantitative cross-sectional study design was implemented. Data was collected from 108 young adults aged between 19 and 29 across different states in Malaysia using the Bedtime Procrastination Scale (BPS), Brief Self-Control Scale (BSCS), Morningness-Eveningness Questionnaire (MEQ), and Zimbardo Time Perspective Inventory (ZTPI) Future Subscale. The convenience sampling method was employed by distributing Qualtrics online survey via email and social media. Multiple Linear Regression analysis was run to examine the hypotheses using SPSS Version 23. Significantly, self-control and chronotype negatively and positively predict bedtime procrastination respectively. Future time perspective is not a significant predictor of bedtime procrastination. This study provides insights into the concept of bedtime procrastination for practitioners to design effective interventions and a direction for future studies to further explore the underlying factors of bedtime procrastination.